Respiratory failure: Classification, Epidemiology and Etiology Review - Vergel Ernest (Newinera Publisher, 2020)
Respiratory failure is a detailed syndrome of the respiratory system failing to perform the function of gas exchange, oxygen intake, and carbon dioxide release. Acute respiratory failure is the most common cause of organ failure in intensive care units (ICUs) with high mortality rates. The classification can be reviewed from two categories of acute respiratory failure and chronic respiratory failure. Acute respiratory failure is often found with the failure of other vital organs. Death is caused by multiple organ dysfunction syndrome (MODS). Etiology can be seen in two categories, namely Central nervous system Depression, Impaired ventilation, Impaired equilibrium perfusion ventilation (V/Q Mismatch), Trauma, Pleural effusion, hemothorax, and pneumothorax, Acute pulmonary disease. Respiratory failure, like failure in other organ systems, can be identified based on clinical features or laboratory tests.